Analysis of turbulent wall jet impingement onto a moving heated body - Cosanay, Hakan; Öztop, Hakan Fehmi; Gur, Muhammed; Bakir, Eda (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this study is to make a numerical analysis of a wall jet with a moving wall attached with a heated body. The hot body is cooled via impinging wall jet. Thus, a jet cooling problem is modeled. The Reynolds number is taken in three different values between 5 x 10(3) <= Re <= 15 x 10(3). The h/H ratio for each value of the Re number was taken as 0.02, 0.04 and 0.0, respectively. Design/methodology/approach Two-dimensional impinged wall jet problem onto a moving body on a conveyor is numerically studied. The heated body is inserted onto an adiabatic moving wall, and it moves in +x direction with the wall. Governing equations for turbulent flow are solved by using the finite element method via analysis and system Fluent R2020. A dynamic mesh was produced to simulate the moving hot body. Findings The obtained results showed that the heat transfer (HT) is decreased with distance between the jet outlet and the jet inlet. The best HT occurred for the parameters of h/H = 0.02 and Re = 15 x 10(3). Also, HT can be controlled by changing the h/H ratio as a passive method. Originality/value Originality of this work is to make an analysis of turbulent flow and heat transfer for wall jet impinging onto a moving heated body.
Keywords: Wall jet; Heat transfer; Impinging flow; Moving block; Moving wall